Soil pH and phosphorus availability regulate sulphur cycling in an 82-year-old fertilised grassland - Wang, Qiqi; Bauke, Sara L.; Döring, Thomas F.; Yin, Jinhua; Cooledge, Emily C.; Jones, Davey L.; Chadwick, David R.; Tietema, Albert; Bol, Roland (Soil biology & biochemistry, 2024)
The application of lime and mineral fertiliser is known to mitigate soil acidification and improve soil quality in improved grasslands. However, the long-term effect of simultaneous lime and fertiliser amendments on soil carbon (C) and sulphur (S) cycling is still poorly understood. To examine if soil pH or nutrient availability are the dominant factors regulating C and S cycling, we evaluated the biodegradation of methionine (organic S), gross S transformation, and microbial S utilisation using 35S and 14C dual-labelling. Soil samples (0–10 cm) were collected from one unfertilised control and five annual limed (Ca) treatments with or without nitrogen (N), phosphorus (P), potassium (K) and sulphur (S) fertilisers (Ca, CaN, CaNP, CaNPKCl, CaNPK2SO4) in an 82-year-old upland grassland experiment in Rengen, Germany. Long-term lime application increased soil pH values but significantly (p < 0.05) decreased soil organic C content. Fertilisation had no significant effect on microbial utilisation of 35S-labelled methionine, while microbial immobilisation of 35SO42− in the limed soils was significantly reduced compared to the control. This is attributed to either the increased soil pH or decreased C availability after liming. Microbial carbon use efficiency (CUE) was significantly higher in soils with applied P fertiliser (i.e., CaNP: 0.66 ± 0.02, CaNPKCl: 0.68 ± 0.02, CaNPK2SO4: 0.65 ± 0.01) compared to the CaN treatment (0.58 ± 0.01). Moreover, compared to CaN, CaNP and CaNPKCl treatments significantly increased gross S turnover, while no significant effects were observed in the CaNPK2SO4 treatment. Soil P deficits decreased microbial CUE and S bioavailability. Although P fertiliser addition alleviated microbial P limitation when N fertiliser was added, S fertiliser (CaNPK2SO4) present constrained S transformation rates. Overall, the importance of P availability for global S cycling in grasslands is shown, especially under N-enrichment conditions. However, the subsequent potential for C loss from long-term liming should be carefully considered in grassland management. Long-term lime plus mineral nutrients fertilisers have a negative effect on microbial inorganic S immobilisation, this is attributed to either the decreased C availability or the increased soil pH from lime addition. While the effects of long-term lime plus mineral nutrients fertilisers on gross S fluxes and carbon use efficiency (CUE) depend on how the mineral nutrient is applied, long-term lime with imbalanced nutrient (e.g. sole N) resulted in the decrease of CUE and gross S transformation because of the low P availability. Long-term lime with both N and P nutrients leads to the increase of CUE and gross S transformation, which is mainly due to high P availability. [Display omitted] •Long-term lime application significantly decreased soil organic carbon content.•Lime plus N (CaN) decreased microbial carbon use efficiency significantly and had lower gross S flux rates.•Microbes are subject to intensive P limitation under treatment CaN.•Microbial inorganic 35S immobilisation decreased with lime input.•S fertiliser (CaNPK2SO4) potentially constrained S transformation rates.